Improving Student Learning Outcomes through the REACT (Relating, Experiencing, Applying, Cooperating, Transfering) Model Based on the Squid Game - Riesma Dwi Mayanti; Dyah Triwahyuningtyas; Melati Sukma Sekar Waluyo; Milenia Nanda Katika; Hestiqoma Maulida (PUSAKA: Journal of Educational Review, 2026)
This study aims to determine the improvement in learning outcomes of third-grade students at SDN Kebonsari 3, Malang City, through the application of the REACT (Relating, Experiencing, Applaying, Cooperating, Transferring) learning model based on the Squid Game game. This study used a descriptive qualitative approach with a Classroom Action Research (CAR) design. The subjects were 25 third-grade students at SDN Kebonsari 3, Malang City. Data were collected from three cycles. The results showed that the REACT learning model based on the Squid Game game resulted in significant improvements, with an average grade point average of 80.2 for the entire class and a completion rate of 88%. Based on these results, it can be concluded that the REACT (Relating, Experiencing, Applaying, Cooperating, Transferring) learning model based on the Squid Game game can improve student learning outcomes in class 3B SDN Kebonsari 3, Malang City, in Mathematics, especially in the topic of presenting data in tables.